THE INFLUENCE OF COLLABORATIVE SUGGESTOPEDIA METHOD AND AUDIO VISUAL MEDIA TOWARD STUDENTS’ SPEAKING ABILITY - Dini Deswarni; Setiawati Setiawati (Universitas Negeri Padang, 2018)
This study aimed to investigate the influence of Collaborative Suggestopedia Method and Audio Visual Media Toward Students’ Speaking Ability at English Department of STAI Hubbulwathan Duri. It was a correlational research design. Then, it also involved 13 students as a sample. Three hypotheses were posed in this study to find out the influence Suggestopedia Method toward students’ speaking ability, audio visual media toward students’ speaking ability, and collaborative suggestopedia method and audio visual media toward students’ speaking ability. The research findings showed that there was an influence of collaborative suggestopedia method and audio visual media toward students’ speaking ability of English Department of STAI Hubbulwathan Duri in academic year 2017/2018. This study used SPSS to analyze the data. The data were correlated by using Pearson Product Moment Correlation (SPSS). Then, the level significance 5% = 0.05 because this study used oral test and Significant F change = 0.04. The degree of correlation between suggestopedia method and audio visual media toward students’ speaking ability is 0.689. Category between 0.5 ≤ r <0.75 is strong. So, based on coefficient correlation (r) value from the formula, 0.689 is strong. It showed that hypothesis alternative (Ha3) was accepted. In conclusion, collaborative suggestopedia method and audio visual media had a strong contribution to students’ speaking ability